2020
DOI: 10.3346/jkms.2020.35.e388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the National PPM Tuberculosis Control Project in Korea: the Korean PPM Monitoring Database between July 2019 and June 2020

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused disruptions to healthcare systems and endangered the control and prevention of tuberculosis (TB). We investigated the nationwide effects of COVID-19 on the national Public-Private Mix (PPM) TB control project in Korea, using monitoring indicators from the Korean PPM monitoring database. Methods The Korean PPM monitoring database includes data from patients registered at PPM hospitals throughout the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…For example, there are expected to be 6.3 million new cases and 1.4 million deaths caused by tuberculosis each year until 2025, setting the efforts to fight the world’s leading infectious disease killer further back [ 79 ]. Moreover, according to research in Korea, the treatment success rate decreased from 90.5% before COVID-19 to 84.6% after COVID-19, with a percentage change of −6.5% at the national level [ 80 ].…”
Section: Antibiotic Prescribing For Covid-19 and The Unnecessary Umentioning
confidence: 99%
“…For example, there are expected to be 6.3 million new cases and 1.4 million deaths caused by tuberculosis each year until 2025, setting the efforts to fight the world’s leading infectious disease killer further back [ 79 ]. Moreover, according to research in Korea, the treatment success rate decreased from 90.5% before COVID-19 to 84.6% after COVID-19, with a percentage change of −6.5% at the national level [ 80 ].…”
Section: Antibiotic Prescribing For Covid-19 and The Unnecessary Umentioning
confidence: 99%
“…For TB cases notified by PPM hospitals, the diagnosis of TB was delayed by 4 days compared to the previous 3 years, whereas it was not delayed for non-PPM hospitals and public health centers, which had fewer TB patients than before. Fortunately, the coverage of acid-fast bacilli smear and culture tests and drug susceptibility testing was above 90% at PPM hospitals, which implies that TB management was carried out at PPM hospitals under the national PPM TB control project in the ROK regardless of the pandemic [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major reason for this may be the maintenance of dedicated TB nurses in PPM hospitals, even when medical resources were concentrated on the COVID-19 response [ 14 ]. In the analysis of TB management indicators at PPM medical institutions, it was reported that the initial TB test rate and the initial compliance rate with treatment guidelines during the COVID-19 pandemic were well maintained, without any substantial differences compared to the rates before COVID-19 [ 23 ]. In addition, it is necessary to consider the decrease in the number of people diagnosed with TB during the COVID-19 pandemic compared to the same period in 2017–2019 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] .…”
Section: Uncited Referencesunclassified